KEANEKARAGAMAN TUMBUHAN AIR DI SUNGAI TEMBAGA PANGKALAN BUN KALIMANTAN TENGAH - pamundhi bekti, Rini; Afri Diyana Dewi, Alif (Program Studi Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas PGRI Banyuwangi, Jalan Ikan Tongkol No 01, Telp (0333) 421593, 428592 Banyuwangi 68416, 2025)
The diversity of aquatic plants plays an important role in maintaining environmental stability around the Tembaga River. This river is one of the natural water bodies with high ecological potential, serving not only as a water source for the local community but also as a habitat for various aquatic organisms. This study aims to identify the diversity of aquatic plant species found in the Tembaga River, Pangkalan Bun, Central Kalimantan. The research was conducted in April 2025. The method used in this study was an exploratory approach through field exploration along the Tembaga River. The results showed that there are nine types of aquatic plants found in the Tembaga River: Salvinia molesta (Kiambang), Pistia stratiotes (Kiapu), Eichhornia crassipes (Eceng Gondok), Nymphaea pubescens (Teratai), Ipomoea aquatica (Kangkung Air), Stenochlaena palustris (Kelakai), Leersia hexandra (Gerigit), Cyperus platystylis (Rumput Para), Limnocharis flava (Genjer), and Monochoria vaginalis (Eceng Padi). Keyword: Diversity, Aquatic Plants, Tembaga River